2017
DOI: 10.1111/jfbc.12428
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abiotic elicitation on the quality and antioxidant potential of lettuce and endive during storage

Abstract: Changes in polyphenol oxidase and peroxidase activities, total phenolic compounds (TPC), vitamin C content, antioxidant activity, as well as overall visual quality and color parameters occurring during 4 days of storage were evaluated in lettuce and endive elicited with jasmonic acid (JA) and arachidonic acid (AA). The content of ascorbic acid in elicited with 100 µM AA2 and jasmonic acid (1 µM—JA1 and 100 µM –JA2) lettuce leaves at the end of the storage was significantly higher than in the control. Surprisin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(74 reference statements)
1
1
0
Order By: Relevance
“…In the case of green leafy plants, special attention has been focused on the a* index, which indicates green-red color. In our previous research, elicitation with arachidonic acid and jasmonic acid did not cause significant changes in the color parameters of fresh leafy vegetables like lettuce or endive [30,31]. The present study indicated that fresh lovage leaves elicited with YE were characterized by brighter color, and both the YE-elicited and JA-elicited plants had a greater proportion of yellow color compared to the control (Table 2).…”
Section: Discussionsupporting
confidence: 58%
“…In the case of green leafy plants, special attention has been focused on the a* index, which indicates green-red color. In our previous research, elicitation with arachidonic acid and jasmonic acid did not cause significant changes in the color parameters of fresh leafy vegetables like lettuce or endive [30,31]. The present study indicated that fresh lovage leaves elicited with YE were characterized by brighter color, and both the YE-elicited and JA-elicited plants had a greater proportion of yellow color compared to the control (Table 2).…”
Section: Discussionsupporting
confidence: 58%
“…The highest antioxidant activity was exhibited by 50 and 100 mM elicitor-treated extract harvested on day 7 and 3, respectively, while the lowest antioxidant activity was exhibited by both 50 and 100 mM elicitor-treated extracts harvested on day 15 (Karalija et al, 2019). Another antioxidant potential study using lettuce and endive showed that, 1 µM of JA-treated samples had the highest antioxidant activity after being stored for 4 days while 100 µM of JA-treated samples had the highest antioxidant activity for lettuce and endive after being stored for 0 and 2 days, respectively (Złotek, 2017). In addition, cultures of A.…”
Section: Antioxidant Activities Of a Indica Extractsmentioning
confidence: 98%